"Look into the Darkness": Mark Jarman's Unholy Sonnets. (March 2018) - Steinberg, Gillian
Mark Jarman's Unholy Sonnets work in dichotomies, drawing on both Renaissance and Modern poetics; biblical texts with complex approaches to faith, especially the books of Job and Ecclesiastes; strict form and formal experimentation. A close examination of the contradictory impulses in Jarman's work illustrates his unique connection to John Donne, whose Holy Sonnets engage with a silent God. Jarman extends this tradition into modernity, identifying, through subtle wordplay, allusion, and religious tradition, the deficiencies of human language and the difficult but worthwhile endeavor of searching for, and occasionally finding, communion with God.